Evaluation of Exertional Ventilatory Parameters Using Oscillometry in COPD - Yamamoto, Yuji (Int J Chron Obstruct Pulmon Dis, 2020)
BACKGROUND: Oscillometry is a tool to measure respiratory impedance that requires minimal patients’ effort. In patients with chronic obstructive pulmonary disease (COPD), the correlation of respiratory impedance at rest with exertional ventilatory parameters, including exercise tolerance, has scarcely been reported. In addition, the utility of oscillometric parameters might differ between the inspiratory and expiratory phases due to airflow obstruction during expiration, but the hypothesis had not been validated. The aim of the present study was to investigate whether oscillometric parameters are associated with exertional ventilatory parameters in patients with COPD. METHODS: Fifty-five subjects with COPD who attended clinics at the National Hospital Organization Osaka Toneyama Medical Center performed spirometry, oscillometry, and cardiopulmonary exercise testing (CPET) within 2 weeks. The correlations between parameters of spirometry, oscillometry, and CPET were analyzed using Spearman’s rank correlation coefficient, univariate, and multivariate analyses. RESULTS: Respiratory reactance had better correlations with the CPET parameters than respiratory resistance. Moreover, inspiratory reactance at rest correlated with the CPET parameters stronger than expiratory reactance. In particular, inspiratory resonant frequency (Fres-ins) correlated with peak oxygen uptake (r(S)=−0.549, p<0.01) and dead space to tidal volume ratio at peak exercise (r(S)=0.677, p<0.01) and the best predicted expiratory tidal volume (V(T) ex) at peak exercise of all the oscillometric parameters (r(S)=−0.679, p<0.01). However, the correlation between Fres-ins and V(T) ex at peak exercise became weak in subjects with severe and very severe COPD during exercise. CONCLUSION: Measurement of respiratory reactance is useful for the effortless evaluation of not only exertional ventilatory parameters but exercise tolerance in patients with COPD. The correlation of respiratory impedance with exertional ventilatory parameters can become weak in patients with advanced COPD; thus, the measurement of oscillometry might not be appropriate for evaluating exertional ventilatory parameters of patients with advanced COPD.